Zmiany na uczelni - ku organizacji hipertekstowej - Leja, Krzysztof (University in transition - the way to hypertext organization, 2006)
The author deals with the challenges in front of the contemporary university as an organization created knowledge-based society. In author opinion university organizational structures do not favour effective transfer of knowledge. Hypertext model of organization by Nonaka and Takeuchi has been proposed to implement to the university. In conclusion the author postulate to look for new organization forms to implement them to the university. Hypertext organization is one of the solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 241-248